Thinking, fast and slow - Kahneman, Daniel, 1934- (Farrar, Straus and Giroux, 2011)
Kahneman exposes the extraordinary capabilities and also the faults and biases of fast thinking, and the pervasive influence of intuitive impressions on peoples' thoughts and choices.